An IDS for DDoS Attacks in SDN using VGG-Based CNN Architecture - Muhammad, Mamdouh; Alshraa, Abdullah; German, Reinhard (The 31st International Conference on Software, Telecommunications and Computer Networks (SoftCOM 2023), 2023)
Keywords: Software Defined Networking; Denial-of-service attack; Deep Learning; Transfer learning; Feature extraction; Intrusion detection

Cybersecurity strategies for smart grids: Leveraging agile IoT and IIoT integration - Alshraa, Abdullah; Muhammad, Mamdouh; German, Reinhard (IGI Global, 2024)
The incorporation of information and communication technologies (ICT) into power grids has brought a new generation in energy management, known as smart grids. This digital transformation has also raised new challenges to cybersecurity. This chapter presents the architecture and cybersecurity interplay within smart grids, highlights the need to secure critical infrastructure, and outlines the security requirements and the importance of availability, integrity, and confidentiality. Also, it discovers potential cyber-threats and vulnerabilities inherent in smart grids and analyzes historical incidents to provide insight into real-world implications. Moreover, the strategies for safeguarding smart grids components, such as supervisory control and data acquisition (SCADA) and industrial control systems (ICS), are discussed, alongside a unified framework to address privacy concerns. Finally, the chapter predicts future trends, identifies pioneering issues, and draws tracks for continuous research and development to strengthen smart grids' resilience against evolving threats.
CRIS-Team Scopus Importer:2024-08-16

Survey of Cybersecurity in Smart Grids Protocols and Datasets - Muhammad, Mamdouh; Alshraa, Abdullah; German, Reinhard (Procedia Computer Science, 2024)
Smart grids are two-way communications grids that converge Information Technology (IT) and Operational Technology (OT) to transfer energy-related information between different industry components within the grid. Smart grids have changed the energy sector by increasing sustainability, efficiency and integrating renewable energy sources. However, smart grids are vulnerable to IT-related attacks because they rely on Information and Communication Technology (ICT). By surveying relevant papers and evaluating accessible statistics, this study explores cybersecurity in smart grids by examining current communication protocols and standards. We carefully compile various datasets with general information about four of the most smart grid-related datasets. Our study and conclusions address the key components of a smart grid and offer information that can help create cybersecurity plans specifically for smart grids. This research contributes to the discourse on smart grid security, which is important for preserving the stability of contemporary energy systems.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Cyber-Physical Systems; cybersecurity; Information Technology; IT/OT convergence; smart grids